TGT Type Cooperative Learning Assisted by Quizizz: Study of Students' Physics Cognitive Abilities on the Material of Motion of Objects - Untajana, Sally E.; Dulhasyim, Ashari Bayu P.; Telapary, Aprillia F.; Kelelufna, Vantri Pieter (Pascasarjana, Mataram University, 2024)
This study aims to analyze the effect of the TGT type cooperative learning model assisted by the quizizz application in improving students' physics cognitive abilities in the material of motion of objects. The type of research used in this study is a quantitative descriptive research type. The design used in this study is the One-Group Pretest-Posttest Design. The subjects in this study were 23 people. The data for this study were collected through test and non-test instruments, the test instrument was in the form of an initial test and a final test, while the non-test instrument was in the form of student worksheets and tournament results. The results of the study showed that the initial abilities of students before being taught using the TGT type cooperative learning model assisted by the quizizz application were proven to be in the failing qualification with an achievement score of 24.08. The cognitive abilities of students during the learning process assessed in the LKPD and tournament obtained completeness from all groups that were in the sufficient qualification with an average value of 74.37. The average score of the final test achievement of students was 81.17 where 1 student was in very good qualification, 10 students were in good qualification and 12 other students were in sufficient qualification. Meanwhile, the results of the analysis of the increase in students' cognitive abilities in the N-gain test obtained a value of >0.74. This result was obtained because of the treatment given, with the TGT type cooperative learning model assisted by the quizizz application. Thus it can be concluded that through the use of the TGT type cooperative learning model assisted by the quizizz application in physics learning is complete on the material of motion in objects